Pengaruh Corporate Social Responsibility terhadap Kinerja Keuangan Perusahaan Pertambangan Batu Bara (The Effect of CSR on the Financial Performance of Coal Mining Companies) - Nurul Hidayah; Suparna Wijaya (STIE Malangkucecwara, 2022)
Instead of using conventional thinking that emphasizes profit, companies nowadays choose to prioritize their long-term programs such as corporate social responsibility (CSR). This research aims to determine the effect of CSR disclosure on financial performance projected by return on assets (ROA) and return on equity (ROE) in coal mining companies listed on the Indonesia Stock Exchange in 2017-2019. Sampling was done by purposive sampling method and obtained 15 companies with a data pool for 3 years. The data analysis method used in this research is simple linear regression test. A simple regression test was performed on 2 equations with different dependent variables. The result of this research indicates that CSR disclosure has no significant effect on ROA and ROE